2017
DOI: 10.1111/imre.12220
|View full text |Cite
|
Sign up to set email alerts
|

Becoming Overweight without Gaining a Pound: Weight Evaluations and the Social Integration of Mexicans in the United States

Abstract: Mexican women gain weight with increasing duration in the United States. In the United States, body dissatisfaction tends to be associated with depression, disordered eating, and incongruent weight evaluations, particularly among white women and women of higher socioeconomic status. However, it remains unclear how overweight and obesity is interpreted by Mexican women. Using comparable data of women ages 20–64 from both Mexico (the 2006 Encuesta Nacional de Salud y Nutricion; N=17,012) and the United States (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 90 publications
1
6
0
Order By: Relevance
“…The finding that acculturative stress is negatively associated with eating disorder symptoms is consistent with other recent research that has examined acculturative stress but not acculturation (Claudat et al, 2016;Menon & Harter, 2012;Van Diest et al, 2014). Similarly, the finding that acculturation is positively associated with some symptoms of eating disorders is consistent with research that has considered acculturation but not acculturative stress (Altman et al, 2017;Poloskov & Tracey, 2013;Warren et al, 2005). However, this study stands apart from the few studies that have simultaneously examined acculturation and acculturative stress (Gordon et al, 2010;Warren & Rios, 2013) by testing and finding support for the hypothesis that acculturative stress mediates the association between acculturation and eating disorder symptoms.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The finding that acculturative stress is negatively associated with eating disorder symptoms is consistent with other recent research that has examined acculturative stress but not acculturation (Claudat et al, 2016;Menon & Harter, 2012;Van Diest et al, 2014). Similarly, the finding that acculturation is positively associated with some symptoms of eating disorders is consistent with research that has considered acculturation but not acculturative stress (Altman et al, 2017;Poloskov & Tracey, 2013;Warren et al, 2005). However, this study stands apart from the few studies that have simultaneously examined acculturation and acculturative stress (Gordon et al, 2010;Warren & Rios, 2013) by testing and finding support for the hypothesis that acculturative stress mediates the association between acculturation and eating disorder symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…However, eating disorder symptoms among Latinas have been found to be comparable, and at times higher, than their non-Hispanic, White counterparts (Stein et al, 2019). For example, Altman et al (2017) compared Mexican women living in the US to those living in Mexico and found that those in the US were more likely to inaccurately describe themselves as overweight, suggesting a negative influence of US culture on their body image. Poloskov and Tracey (2013) found that Latina college students who were more acculturated to the dominant White culture of the US were more dissatisfied with their bodies because they had internalized the thin body ideal.…”
mentioning
confidence: 99%
“…Our analysis did not find strong evidence that cultural identity or years in the U.S. were associated with perceptions of a health body size in South Asians. Although empiric data have shown that body size ideals differ across cultures (McCabe et al, 2015) and that immigrants may adopt the body size norms of their host culture over time (Altman et al, 2017), the associations between acculturation with body size norms and behaviors have not been consistent. Others have found that psychosocial stressors, socioeconomic status, and other cognitive processes may be more predictive of body size ideals or weight-related behaviors in immigrant adolescents and that these factors may also interact with acculturation and immigrant generation (Fialkowski et al, 2015; Sutin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies stratified Brazilian immigrants in their analyses [30,47]. Regarding country of origin of the immigrants studied, 14 studies involved Mexicans only [15,26,27,42,43,52,64,65,[74][75][76][77]79,81], 11 Mexicans and other Latinos [16,33,34,36,49,51,54,61,63,66,67], 10 investigated immigrants from South and Central America (Brazil [30,47], Haiti [30,32], El Salvador [30,40], Colombia [30], Guatemala [30,40], Dominican Republic [30,46], Honduras [30,40], Peru [40], Bolivia [40], Puerto Rico [32,46], Mexico [46], Guyana [82] and other unspecified coun-tries [32,35,…”
Section: Study Characteristicsmentioning
confidence: 99%